(untitled) (International Journal of Food and Nutritional Sciences, 2024)
"Donation for Good Cause" is a platform that simplifies donations, allowing users to give items like food, clothing, and funds in one place. It assists communities by directing surplus goods to organizations such as orphanages, old age homes, and shelters, thus reducing waste. Donors register with their contact details and post donations in the "Available Donations" section. Recipients, including non-profits and shelters, verify their identity and organization during registration. After approval, they can browse and claim the items they need. For example, a donor offering food specifies the type, quantity, and location, making it easier for recipients to collect. This platform helps reduce waste and ensures resources are efficiently distributed to those in need, connecting donors directly with organizations that serve underserved communities.